2016
DOI: 10.1016/j.bpj.2016.11.003
|View full text |Cite
|
Sign up to set email alerts
|

A Unique Light-Driven Proton Transportation Signal in Halorhodopsin from Natronomonas pharaonis

Abstract: Halorhodopsin (HR) is a seven-transmembrane retinylidene protein from haloarchaea that is commonly known to function as a light-driven inward chloride pump. However, previous studies have indicated that despite the general characteristics that most HRs share, HRs from distinct species differ in many aspects. We present indium-tin-oxide-based photocurrent measurements that reveal a light-induced signal generated by proton release that is observed solely in NpHR via purified protein-based assays, demonstrating t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…The same phenomenon was observed in NpHR (Fig. 4c , middle), which was reported to undergo a proton circulation on the cytoplasmic side 27 . The same measurement was conducted on the HEBR-NpHR fusion protein (Fig.…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…The same phenomenon was observed in NpHR (Fig. 4c , middle), which was reported to undergo a proton circulation on the cytoplasmic side 27 . The same measurement was conducted on the HEBR-NpHR fusion protein (Fig.…”
Section: Resultssupporting
confidence: 81%
“…The functionality of HEBR-NpHR was probed with the whole cell E. coli pH and protein-based photocurrent assays that we previously adopted and developed 27 . After expressing HEBR-NpHR in E. coli , the cells were centrifuged and resuspended in a non-buffer solution.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Their rhodopsins and their applications have been deeply studied. Besides, several studies have focused on the biotechnological potential of its enzymes [7][8][9][10][11][12][13][14][15]. On the other hand, several culture-independent studies have also shown the presence of members of the genus Natronomonas in different environments from widely separated sites, such as hypersaline and alkaline lakes, solar salterns, saline-alkaline soils, and sediments or oil fields [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31], supporting the widespread distribution of species of this genus.…”
Section: Introductionmentioning
confidence: 99%
“…Second, halorhodopsin, a light-driven inward chloride pump activated by 580 nm light, is to maintain cellular osmotic pressure under extreme salinity 6 . In addition, we recently reported that halorhodopsin pumps chloride through a proton partnership 7 and thus, its physiological role requires more investigation. The third and fourth types of rhodopsins are the red light-sensing (585 nm) sensory rhodopsin I (SRI) and the blue light-sensing (485 nm) sensory rhodopsin II (SRII), which mediate photo-attractant and photorepellent responses, respectively 8–10 .…”
Section: Introductionmentioning
confidence: 99%